Rapid automatic naming and phonological awareness deficits in preschool children with probable developmental coordination disorder - Cheng, Hsiang-Chun; Cherng, Rong-Ju; Yang, Pei-Yu (Frontiers in Pediatrics, 2022)
Children with developmental coordination disorder (DCD) have been reported to have a higher risk of dyslexia than children with typical development (TD). Phonological awareness (PA) and Rapid Automatic Naming (RAN) are known to be predictive of children’s reading development. The present study examined PA and RAN in preschool children with and without DCD in Taiwan. The participants were 704 children aged 5-6 years old from 25 preschools in Taichung City. The DCD children performed more poorly than the TD children on the PA and the RAN tests. Put in deficit terms, 22% of the TD children, but 48% of the DCD children, had a single or dual PA/RAN deficit. Further, it was manual dexterity that bore the unique relationship with RAN. Automatic visual perceptual-motor coordination may be the common processing component that underlies RAN and DCD. The early visual perceptual-motor profile of the DCD children has not been well recognized before.